Review of human-animal interactions and their impact on animal productivity and welfare. - Idrus, Zulkifli (BioMed Central, 2013)
Humans and animals are in regular and at times close contact in modern intensive farming systems. The quality of human-animal interactions can have a profound impact on the productivity and welfare of farm animals. Interactions by humans may be neutral, positive or negative in nature. Regular pleasant contact with humans may result in desirable alterations in the physiology, behaviour, health and productivity of farm animals. On the contrary, animals that were subjected to aversive human contact were highly fearful of humans and their growth and reproductive performance could be compromised. Farm animals are particularly sensitive to human stimulation that occurs early in life, while many systems of the animals are still developing. This may have long-lasting impact and could possibly modify their genetic potential. The question as to how human contact can have a positive impact on responses to stressors, and productivity is not well understood. Recent work in our laboratory suggested that pleasant human contact may alter ability to tolerate various stressors through enhanced heat shock protein (hsp) 70 expression. The induction of hsp is often associated with increased tolerance to environmental stressors and disease resistance in animals. The attitude and consequent behaviour of stockpeople affect the animals’ fear of human which eventually influence animals’ productivity and welfare. Other than attitude and behaviour, technical skills, knowledge, job motivation, commitment and job satisfaction are prerequisites for high job performance.